Institutional delivery service utilization and associated factors in Ethiopia: a systematic review and META-analysis - Adane Nigusie; Telake Azale; Mezgebu Yitayal (BMC, 2020)
Abstract Background There is wide variation in the utilization of institutional delivery service in Ethiopia. Various socioeconomic and cultural factors affect the decision where to give birth. Although there has been a growing interest in the assessment of institutional delivery service utilization and its predictors, nationally representative evidence is scarce. This study was aimed to estimate the pooled national prevalence of institutional delivery service utilization and associated factors in Ethiopia. Methods Studies were accessed through PubMed, Cochrane library, Web of Science, and Google Scholar. The funnel plot and Egger's regression test were used to see publication bias, and I-squared statistic was applied to check heterogeneity of studies. A weighted Dersimonian laired random effect model was applied to estimate the pooled national prevalence and the effect size of institutional delivery service utilization and associated factors. Result Twenty four studies were included in this review. The pooled prevalence of institutional delivery service utilization was 31% (95% Confidence interval (CI): 30, 31.2%; I2 = 0.00%). Attitude towards institutional delivery (Adjusted Odd Ratio (AOR) = 2.83; 95% CI 1.35,5.92) in 3 studies, maternal age at first pregnancy (AOR = 3.59; 95% CI 2.27,5.69) in 4 studies, residence setting (AOR = 3.84; 95% CI 1.31, 11.25) in 7 studies, educational status (AOR = 2.91;95% 1.88,4.52) in 5 studies, availability of information source (AOR = 1.80;95% CI 1.16,2.78) in 6 studies, ANC follow-up (AOR = 2.57 95% CI 1.46,4.54) in 13 studies, frequency of ANC follow up (AOR = 4.04;95% CI 1.21,13.46) in 4 studies, knowledge on danger signs during pregnancy and benefits of institutional delivery (AOR = 3.04;95% CI 1.76,5.24) in 11 studies and place of birth of the elder child (AOR = 8.44;95% CI 5.75,12.39) in 4 studies were the significant predictors of institutional delivery service utilization. Conclusion This review found that there are several modifiable factors such as empowering women through education; promoting antenatal care to prevent home delivery; increasing awareness of women through mass media and making services more accessible would likely increase utilization of institutional delivery.